PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT PACIFIC REMOVINDO DI JAKARTA - Agustina Mogi; Arief Rahman Maulidi (Jurnal Menara, 2026)
This study aims to determine the effect of compensation and work discipline on employee performance at PT. Pacific Removindo in Jakarta. The research uses a quantitative associative approach with a survey method. The sample consists of 76 respondents who are employees of PT. The results showed that partially, compensation has a positive and significant effect on employee performance with the regression equation Y = 23.966 + 0.477 X1, t-value = 2.957 > t-table = 1.996, and a significance of 0.004. Work discipline also has a positive and significant effect on employee performance with the regression equation Y = 12.155 + 0.705 X2, t-value = 5.456 > t-table = 1.996, and a significance of 0.004. Simultaneously, compensation and work discipline have a positive and significant effect on employee performance with the regression equation Y = 7.329 + 0.266 X1 + 0.571 X2. The F-value is 32.204 > F-table = 3.122 with a significance of 0.000, and the coefficient of determination (R²) is 0.469 or 46.9%. This means that 46.9% of the variation in employee performance can be explained by compensation and work discipline, while the remaining 53.1% is explained by other variables not examined in this study. The results show that compensation has a positive and significant effect on employee performance, and work discipline also positively and significantly affects employee performance. Simultaneously, compensation and work discipline have a positive and significant influence on the performance of employees at PT. Pacific Removindo.